+0  
 
0
30
1
avatar

Find EH.

 

 Mar 28, 2021
 #1
avatar+84 
0

Note that the decrease from FD to GH is proportional to the decrease from ED to EG.

 

Since GH is 1/2 of FD(6 is 1/2 of 12), we can deduce that  EG is 1/2 of GD:

 

1/2(ED) = EG

1/2((x+5)+9) = x+5

1/2(x+14) = x + 5

x + 14= 2x + 10

4 = x

 

Since HF is also 9, we can apply the same logic to EH, meaning that EH = x+5

 

EH = x + 5

EH = (4) + 5

EH = 9

 Mar 28, 2021

64 Online Users

avatar
avatar
avatar
avatar
avatar
avatar